Marginalization of Genggong Art in Batuan Villages in the Global Era - Winyana, I Nyoman; Suarka, I Nyoman; Sugiarta, I Gde Arya (International Journal for Educational and Vocational Studies, 2020)
Genggong performance art is a form of art in Batuan Village. Its existence in the midst of community life is closely related to the tourism industry. Its presence is currently increasingly squeezed by the Golbal culture which is not only present from modern (calcic) traditional arts but also contemporary culture. If it is left out it is not impossible that Genggong art will disappear. It can also erase the local cultural identity in Batuan Village. Efforts to optimize Genggong's art at this time are a problem. This not only arises because of internal problems from the Genggong actors themselves, but also externally the network that was cut off was often caused by factors playing in it. The importance of making this Genggong art present in Batuan is none other than the icon of the Batuan Culture village which has become a tourist village, worth fighting for given that cultural richness is a hallmark of genius society. In addition to optimizing the Genggong art, it has the opportunity to be a more useful touristic spectacle. The impact of the Genggong art problem in Batuan Village will also be a pilot project for the arts of the same fortune in the global era. In addition, financially the actors involved in it feel they have the opportunity to earn a fortune and protection. This study uses a cultural study approach that is more focused on solving problems to raise the issue of marginalization with cultural theories. It seems that through qualitative methods explanations can find a deeper analysis. Resolving the Genggong art problem can be a model for other traditional arts that also suffer a similar fate. The findings of this study at least give rise to a new awareness to jointly provide a way out of traditional Balinese art so that it can be enjoyed more broadly over time.